(untitled) (Far Western Review, 2025)
The flipped learning approach (FLA), a technology-driven, active pedagogical model, has been widely researched and adopted globally across all academic levels and disciplines to enhance educational quality. However, in the context of Nepal, the reappears to be a notable lack of studies on FLA. This micro-ethnographic study examined the flipped learning environment and practices in Grade 10 mathematics classrooms in Nepal. One school, a mathematics teacher, and three students were purposively selected as participants. Qualitative analysis of data collected through direct observation and in depth interviews revealed an inadequate environment for adopting FLA, with challenges related to teachers, students, technology, and the school’s support. The study investigated constructivist, inquiry-based, and problem-solving in-class practices, involving active discussions, interactions, group work, completing exercises, and guided problem-solving, that closely aligned with FLA. However, out-class practices were constrained to solving exercises and practicing old question sets due to the deficiency of teachers’ lecture videos. This study suggests that stakeholders in mathematics education should take responsibility to create favorable FL environments for its effective adoption and promote meaningful learning in mathematics.